Elastic Properties of Steel-Cord Rubber Conveyor Belt - Golovanevskiy, Vladimir; Kondratiev, A. (SPRINGER, 2021)
Reinforced with steel-cord rubber conveyor belt (SCB), i.e. a unidirectional composite material (CM) with some of the fundamental mechanical properties values of its reinforcement and matrix differing by a factor of ten thousand, is a key infrastructure component of overland minerals transportation industry. Critically, to date no investigative work has been performed on the mechanical behaviour of SCBs subjected to the extreme dynamic-loading conditions of tropical cyclones, hurricanes, and tornados. Determination of a full suite of elastic characteristics of the belt will enable the study of the mechanical behaviour of SCB subjected to these natural hazardous wind events. We investigate tensile and shear moduli of a commercial SCB with the use of modified standard practices and innovative approaches, including tensile testing and methods of torsion of long straight bar and of square plate. We propose a novel design of mechanical tensometer which allows tensile testing of significantly shorter test specimens as compared with the test specimen dimensions per current standards. Analytically, tensile modulus is determined using the rule of mixtures and shear moduli are calculated based on the variational principles. We find that the tensile modulus of SCB can be determined analytically with high confidence. However, analytically derived in-plane shear moduli values can only be considered as a first approximation and need to be verified experimentally. The results of our work improve understanding of stress-strain state and thus can help predict the mechanical behavior of the SCBs under the irregular and extreme dynamic loading conditions of natural hazardous wind events.